Systemic and mammary inflammation and mammary gland development of Holstein dairy cows around dry-off and calving - J. Gao; T.N. Marins; J.O.S. Calix; Z. Qi; C.G. Savegnago; A.M. Roper; M.W. Woldemeskel; J.K. Bernard; S. Tao (Journal of Dairy Science)
ABSTRACT: This study evaluated systemic and mammary inflammation and the immune cell population and developmental pattern of the mammary gland in Holstein dairy cows transitioning from late lactation to the dry period (LTD, n = 6) and from the dry period to early lactation (DTL, n = 7). All cows were healthy and free of mastitis at enrollment. Mammary biopsies, milk or mammary secretions, and blood samples were collected on d −7, 3, 7, and 15 relative to dry-off and on d −8, 3, 7, and 21 relative to calving. After dry-off, LTD cows had increased circulating concentrations of tumor necrosis factor (TNF)-α, haptoglobin, and fibrinogen, suggesting upregulated inflammation. Protein, SCS, and SNF contents in milk or mammary secretions increased during the early dry period but decreased after calving. In contrast, lactose concentrations in mammary secretions decreased in the early dry period and increased following calving. Skim milk concentrations of TNF-α, IL-10, and haptoglobin increased following dry-off. Consistently, mammary tissue mRNA expression of IL1B and IL10 tended to increase on d 7 and 15 following dry-off, respectively. After calving, mammary alveolar and total cells had higher apoptosis rates. Mammary alveolar, stromal, and total cell proliferation rates peaked on d 7 after dry-off in mammary tissue collected from LTD cows and were greater in the late dry period than early lactation. Mammary mRNA expression of HGF increased on d 7 and 15 after dry-off. Mammary tissue collected in the late dry period had greater gene expression of IGF1, IGF2, PRLR than that collected in early lactation. Mammary tissues collected in the early dry period had greater percentages of CD20+ B lymphocytes, CD172a+ macrophages, and neutrophils than tissues collected during late lactation. Mammary tissues collected in early lactation had greater percentages of CD20+ B lymphocytes, CD3+ T lymphocytes, and CD172a+ macrophages than tissue collected in the late dry period. In conclusion, dairy cows experienced upregulated systemic and mammary inflammation during the early dry period, which warrants further research to elucidate its effect on mammary development. Our data also suggested that the increased mammary growth during the late gestation and early dry periods was mediated by different mechanisms. The concurrent increases in immune cell infiltration and mammary cell proliferation in the mammary gland following dry-off suggest an association between mammary immune responses and growth during the early dry period.